Hyperpolarized NMR Spectroscopy: d‐DNP, PHIP, and SABRE Techniques. Issue 15 (16th July 2018) - Kovtunov, Kirill V.; Pokochueva, Ekaterina V.; Salnikov, Oleg G.; Cousin, Samuel F.; Kurzbach, Dennis; Vuichoud, Basile; Jannin, Sami; Chekmenev, Eduard Y.; Goodson, Boyd M.; Barskiy, Danila A.; Koptyug, Igor V.
Abstract: The intensity of NMR signals can be enhanced by several orders of magnitude by using various techniques for the hyperpolarization of different molecules. Such approaches can overcome the main sensitivity challenges facing modern NMR/magnetic resonance imaging (MRI) techniques, whilst hyperpolarized fluids can also be used in a variety of applications in material science and biomedicine. This Focus Review considers the fundamentals of the preparation of hyperpolarized liquids and gases by using dissolution dynamic nuclear polarization ( d ‐DNP) and parahydrogen‐based techniques, such as signal amplification by reversible exchange (SABRE) and parahydrogen‐induced polarization (PHIP), in both heterogeneous and homogeneous processes. The various new aspects in the formation and utilization of hyperpolarized fluids, along with the possibility of observing NMR signal enhancement, are described. Abstract : Polarized opinions : This Focus Review discusses the development of dissolution dynamic nuclear polarization ( d ‐DNP), signal amplification by reversible exchange (SABRE), and parahydrogen‐induced polarization (PHIP) techniques as effective and promising approaches for signal enhancement in NMR spectroscopy and the production of hyperpolarized contrast agents.